2012
DOI: 10.1002/hup.1276
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Effect of blonanserin on cognitive function in antipsychotic‐naïve first‐episode schizophrenia

Abstract: These results suggest that blonanserin improves some types of cognitive function associated with prefrontal cortical function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 66 publications
1
11
0
Order By: Relevance
“…However, the present study’s results indicated that RIS significantly improved verbal fluency and that the effect size was moderate. BNS exerted improving effects on verbal fluency and executive function, as previously reported 18. A previous study indicated that the effect size of antipsychotic drugs is small in terms of many variables related to the improvement of cognitive function 31.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…However, the present study’s results indicated that RIS significantly improved verbal fluency and that the effect size was moderate. BNS exerted improving effects on verbal fluency and executive function, as previously reported 18. A previous study indicated that the effect size of antipsychotic drugs is small in terms of many variables related to the improvement of cognitive function 31.…”
Section: Discussionsupporting
confidence: 74%
“…In a recent meta-analysis, the effect of BNS was demonstrated to be equal to that of haloperidol and risperidone (RIS) in primary endpoints and superior to haloperidol in improving negative symptoms in patients with schizophrenia 17. Moreover, BNS improved verbal fluency and executive function with first-episode schizophrenia 18. However, to our knowledge, no study has evaluated the effects of BNS on the cognitive and social functions of patients with acute-phase schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…The effect sizes for these changes were in the moderate range (0.58 and 0.62, respectively). All items on the PANSS, SQLS-J, and Clinical Global Impression-Severity of Illness Scale significantly improved after 8 weeks of treatment (all P < 0.01) 42. These results suggest that blonanserin improves some types of cognitive function (letter fluency and executive function) that are associated with prefrontal cortical function in patients with first-episode schizophrenia.…”
Section: Pharmacological Profilementioning
confidence: 70%
“…We recently conducted an 8-week, open-label study to evaluate the effects of blonanserin on clinical efficacy including cognitive function and subjective QOL in patients with antipsychotic-naïve first-episode schizophrenia 42. Cognitive function was assessed with the Brief Assessment of Cognition in Schizophrenia Japanese-language version (BACS-J),43 and subjective QOL was assessed with the Schizophrenia Quality of Life Scale Japanese-language version (SQLS-J) 44…”
Section: Pharmacological Profilementioning
confidence: 99%
“…When a diagnostic instrument is culture-fair, the results can be subjected to analysis in children of different ethnic and cultural groups in South Africa and in other countries. Besides its extensive use in the USA (Gendle et al, 2013;Solanto et al, 2007) and Europe (Baker et al, 1996;Cazalis et al, 2003;Roussos, Giakoumaki, Pavlakis, and Bitsios, 2008;Rowe, Owen, Johnsrude, & Passingham, 2001), it also has been used successfully in Eastern, Middle Eastern and South American countries (Chang et al, 2011;Tenjin et al, 2012;Yanez-Tellez et al, 2012) and many more. No studies using the ToL could be found for populations on the African continent.…”
Section: Culture-fairness Of the Tower Of Londonmentioning
confidence: 99%